Preventing Transport of Airborne Contaminants in Hospital Facilities - A measurement study of particles, air flows and pressure conditions - Rehn, Daniel (My University, 2016)
In hospitals there is always a need for controlling the spread of airborne disease, to ensure patient and personnel health. This thesis studies how ventilation and building technology can be used to limit the spread of infections within hospitals, the report specifically focuses on how an existing hospital performs. The study's focus is pressurization, particle levels and possibilities to control these two factors. One way to control the pressurization is through air flow balance, supplying more air to room than what is exhausted will create a overpressure. Controlling these might lead to improvements to the facilities. The report of a literature study to form a theoretical basis for the report, study visits to a hospital to investigate how the logistic patterns look and measurements in order to quantify the problems. The particle and pressure measurements indicate that there is limited control of the contaminant transport in the facilities. Results and analysis include possible improvements both through renovation and for design of new buildings.
Keywords: Samhällsbyggnadsteknik; Building Futures; Civil Engineering; Building Futures